Phytochemistry of Ziziphus Mauritiana; its Nutritional and Pharmaceutical Potential - Shumaila Zulfiqar Butt; Shabbir Hussain; Khurram Shahzad Munawar; Affifa Tajammal; Muazzam Ali Muazzam (Scientific Inquiry and Review, 2021)
Current studies were performed to overview the phytochemistry, nutritional and medicinal value of Ziziphus mauritiana (commonly known as Ber in Pakistan). The leaves of Z. mauritiana are comprised of proteins, amino acids, alkaloids, terpenoids, fibers, flavonoids, tannins, glycosides, and phenolic compounds. The leave majorly demonstrate the presence of α-linolenic acid, plamitic acid and methyl stearate in n-hexane, chloroform and methanol extracts. The seed contains the highest content of carbohydrate (63.24%) and calorific value (411.61 kJ) while its fruit shows the highest quantity of moisture. Its fruit is slightly acidic (pH around 4.77) and rich in nutrients including proteins, carbohydrates vitamin C and minerals (Fe, Zn, Cu, Na, K, Ca, P). The fruit provides energy of 1516-1575 kJ per its 100 g. Z. mauritiana displays antibacterial, antioxidant and anti-inflammatory activities. Its leaves are used for treating tuberculosis, small pox, burning sensations, dysentary asthma, fever, liver issues, infections and blood relating diseases. Root bark of this plant shows good effectiveness as analgesic, anti-inflammatory and anti-allergic agent. The plant displays strong antioxidant potential and excellent H2O2 scavenging activities.Copyright (c) The Authors